Albania Country Procurement and Contract Implementation Review - World Bank (World Bank, Washington, DC, 2018)
This report presents the World Bank and Islamic Development Bank, collectively the Banks, teams’ review and assessment of Albania country procurement and contract implementation CPCI), including for projects and civil works contracts financed by the Banks. This report focuses on the most critical findings and it summarizes key recommendations. Detailed analysis and recommendations are provided in the report. The CPCI aims to provide the Government of Albania (GoA) with an updated diagnosis of the strengths and weaknesses of public procurement and to make specific recommendations and practical suggestions for achieving increased effectiveness in service delivery, through an improved public procurement system, planning and implementation as well as contract management. The report also presents specific analysis of implementation of projects and procurement of contracts financed by the Banks and it discusses more specifically some questions raised by the GoA regarding options to centralize procurement of donors’ financed projects. The report has nine sections: I. introduction, II. procurement legal and regulatory framework, III. institutional framework and management capacity, IV. procurement operation and market practices, V. contract implementation and management, VI. public financial management relevant to procurement, VII. integrity and transparency relevant to procurement, VIII. performance of World Bank and Islamic Development Bank portfolios, and IX. recommendations and suggested action plan.